Tax Shifting and Incentives for Biodiversity Conservation on Private Lands. Issue 2 (26th July 2017) - Schuster, Richard; Law, Elizabeth A.; Rodewald, Amanda D.; Martin, Tara G.; Wilson, Kerrie A.; Watts, Matthew; Possingham, Hugh P.; Arcese, Peter
Abstract: Conservation in human‐dominated landscapes is challenging partly due to the high costs of land acquisition. We explored a property tax mechanism to finance conservation easements or related contracts as a partial‐property acquisition strategy to meet Convention on Biological Diversity (CBD) treaty targets to conserve critically imperiled coastal Douglas fir ecosystems in Canada. To maximize cost‐efficiency, we used systematic planning tools to prioritize 198, 058 parcels for biodiversity values, estimated the cost of eliminating property tax on high‐priority parcels to engage land owners in conservation, and then calculated the tax increase on nonpriority parcels necessary to maintain tax revenue. Marginal tax rate increases of 0.13, 0.21, and 0.51% on nonpriority parcels were necessary to offset the elimination of tax revenue on ∼21, 000 ha of high‐priority parcels, and potentially sufficient to increase area protection from 9% to 17% to meet CBD targets given uptake rates of 100, 50, or 25%, respectively. Sensitivity analyses suggest uptake rates of 30% to 40% could allow government to achieve a 17% target with 30% of the planning area prioritized for inclusion in a property tax mechanism. Our results suggest prioritizing parcels for biodiversity value and commensurate "tax shifting" may offer an efficient route to conservation on private land.